Sistem Pendukung Keputusan Penerimaan Siswa Baru di MTS Bustanul Ulum Menggunakan Metode SMART (Simple Multi-Attribute Rating Technique) - Zaehol Fatah; Akhlis Munazilin; Lukman Aliyasin (G-Tech: Jurnal Teknologi Terapan, 2024)
Education is a fundamental need for every individual that must be fulfilled to lead a life. Furthermore, education plays a crucial role in shaping one's personality, enabling them to become a beneficial member of society and the nation. Madrasah Tsanawiyah Bustanul Ulum is a private junior high school that employs a ranking method for new student admissions, utilizing Microsoft Excel for the current selection system. However, this method consumes a considerable amount of time due to various criteria. The solution to address this issue is the implementation of a multi-criteria decision support system. This research employs the SMART (Simple Multi-Attribute Rating Technique) method because it facilitates accurate decision-making